2014
DOI: 10.1007/s11605-013-2423-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ISGLS Definition of Posthepatectomy Liver Failure and Its Effect on Outcome in Patients with Hepatocellular Carcinoma

Abstract: The ISGLS definition of PHLF was associated with OS and RFS in HCC patients, and long-term survival will be improved by reducing the incidence of PHLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 26 publications
7
66
1
Order By: Relevance
“…Liver surgery has led to impressive reductions in mortality and morbidity over the last decade, and is the treatment of choice for a range of primary and secondary liver diseases [1,2,3]. On the other hand, as hepatectomy for hepatocellular carcinoma is often undergone by patients with insufficient hepatic reserve for the future liver remnant, posthepatectomy liver failure is a matter of alarming concern [4].…”
Section: Introductionmentioning
confidence: 99%
“…Liver surgery has led to impressive reductions in mortality and morbidity over the last decade, and is the treatment of choice for a range of primary and secondary liver diseases [1,2,3]. On the other hand, as hepatectomy for hepatocellular carcinoma is often undergone by patients with insufficient hepatic reserve for the future liver remnant, posthepatectomy liver failure is a matter of alarming concern [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fukushima et al [5] reported major hepatectomy, intraoperative blood loss (>1,000 mL) and stage 3 fibrosis as independent risk factors for PHLF, according to the ISGLS definition [5]. Both the Iguchi and Fukushima groups reported that PHLF was associated with recurrence and survival after resection.…”
Section: Discussionmentioning
confidence: 99%
“…Although various treatment strategies, such as liver resection, local ablation, transcatheter arterial chemoembolization and liver transplantation are available for HCC, liver resection is widely performed as the first-line option because of its low morbidity and mortality rates [2-4]. However, the morbidity rates after hepatectomy remain high [5-7]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations